STATISTICAL ESTIMATION OF THE GREEN GROWTH IN UKRAINE - G. Yeliseyeva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
A set of indicators proposed by the OECD that assesses economic opportunities arising from the green growth as well as helps policy-making concerning environmental issues, in particular indicators on technology and innovation, production and consumption of environmental goods and services, environmentally related prices and transfers as well as associated to green growth financial flows, have been studied in detail in this article. The results of the comparison analysis of the application of the abovementioned indicators by the Czech Republic, Denmark, Germany, the Netherlands and Korea are presented in the article. Based on the performed analysis possible application of the proposed by OECD set of indicators to the Ukraine’s national context has been explored. Proposed set of green growth indicators can be applied in Ukraine, however further development is required to enhance the statistical data accounting and availability. Among the main challenges to the implementation of such system in Ukraine is the lack of data as well as medium compliance of the Ukraine’s Environmental Accounts with the European regulation, which complicates the development of national policy towards green economy and the international comparison.